The CISO evolution : Business knowledge for Cybersecurity Executives - Sharp, Matthew K; Lambros, Kyriakos P (2022)
"Cybersecurity is the protection of computer systems and networks from the theft of or damage to their hardware, software, or electronic data, as well as from the disruption or misdirection of the services they provide. A CISO (chief information security officer) is the senior-level executive within an organization responsible for establishing and maintaining the enterprise vision, strategy, and program to ensure information assets and technologies are adequately protected. The CISO directs staff in identifying, developing, implementing, and maintaining processes across the enterprise to reduce information and IT risks."--
Includes index.
Keywords: Chief information officers; Computer security; Management information systems -- Security measures